2016
DOI: 10.1001/jamaoncol.2016.0004
|View full text |Cite
|
Sign up to set email alerts
|

Durable Responses With Maintenance Dose-Sparing Regimens of Romidepsin in Cutaneous T-Cell Lymphoma

Abstract: Decreasing the frequency of infusions in patients with MF or SS who achieve a response with romidepsin therapy may provide a practical strategy to prolong response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
2
18
0
Order By: Relevance
“…In our study the modified Severity‐Weighted Assessment Tool was not used, because the study was retrospective and this score was not systematically indicated in the medical records. Our study confirms the existence of long‐term responders (especially in patients with MF) . Although romidepsin seems to be more effective for MF, we did not find any predictive factor for efficacy.…”
supporting
confidence: 83%
“…In our study the modified Severity‐Weighted Assessment Tool was not used, because the study was retrospective and this score was not systematically indicated in the medical records. Our study confirms the existence of long‐term responders (especially in patients with MF) . Although romidepsin seems to be more effective for MF, we did not find any predictive factor for efficacy.…”
supporting
confidence: 83%
“…Cutaneous T cell lymphoma (CTCL) is a kind of extranodal non‐Hodgkin T cell lymphoma characterized by the presence of malignant T cells in the skin. Among various forms of CTCLs, mycosis fungoides (MF) and the leukaemic variant Sézary syndrome (SS) are the most prevalent forms of CTCL . Although some induction chemotherapies have been approved for the treatment of CTCL, the responses of many patients are typically short‐lived .…”
Section: Introductionmentioning
confidence: 99%
“…Among various forms of CTCLs, mycosis fungoides (MF) and the leukaemic variant Sézary syndrome (SS) are the most prevalent forms of CTCL. 1,2 Although some induction chemotherapies have been approved for the treatment of CTCL, the responses of many patients are typically short-lived. 3 Therefore, developing effective chemotherapies for CTCL is extremely urgent.…”
Section: Introductionmentioning
confidence: 99%
“…3 Several genetic variants have been found to be strongly associated with risk of melanoma using a candidate gene approach. The aim of our study was to identify, novel CM genetic factors, using all candidate genes encompassed in the MelGene database (www.melgene.org), a comprehensive online database, [3][4][5] by assessing their association in the largest genome wide association study (GWAS) published up to date. 6 Promising signals were selected for replication in UK-Biobank (https://www.ukbioba nk.ac.uk/), a prospective cohort study of 500 000 participants and two independent samples of CM patients and healthy controls from Greece and Cyprus.…”
Section: Supporting Informationmentioning
confidence: 99%
“…1 In the last 10 years, the need for an MF maintenance treatment has been investigated in the literature, with most of experiences focusing on the early stages 2,3 and a few on the advanced phases. 2,4 Encouraging results on the chances of achieving lasting responses after the treatment have been reported in patients on brentuximab vedotin. 5 However, only a small cohort of patients have been enrolled in clinical trials 5 ; thus, no definitive conclusions can be drawn.…”
mentioning
confidence: 99%